COMPUTERIZED MAINTENANCE MANAGEMENT SYSTEM FOR A CONSOLIDATED PROGRAM - Ibey, Andrew; King, Doug; Hsieh, Tony; Hutnan, Tim; Dixon, John; Soet, Richard (CMBES Proceedings, 2014)
Clinical Engineering (CE) departments require a documentation system, whether it’s paper, computerized or cloud based. The Computerized Maintenance Management System (CMMS) database has been described as early as 1985 (Kresch, 1985). Others have documented the functionality of the CMMS as a repository for: service history data, preventive maintenance schedules, warranty periods, and alerts & hazards (Cohen, 2001). When venturing into a consolidated operation the CMMS provides a focus point for conversations about business processes, operational requirements, technology management, and support of clinical services. This paper will focus on the planning and implementation of a CMMS implementation; highlight some of the practical challenges associated with combining operations and data from disparate CMMS systems into one database.